Cover crop effects on infiltration, aggregate stability, and water retention in the Lower Mississippi River Valley - Shelby Lebeau; Kristofor R. Brye; Mike B. Daniels; Lisa S. Wood (Agrosystems, Geosciences & Environment, 2023)
Abstract Cover crops are widely considered to improve soil health in the form of erosion control, organic matter additions, and improving water‐holding capacity. Despite the generally well‐documented benefits, cover crops remain under‐studied in the Lower Mississippi River Valley (LMRV), an area historically dominated by intensive cultivated agriculture, with soils prone to erosion, and where the need for irrigation has led to unsustainable aquifer withdrawals. The objective of this study was to evaluate cover crop (with cover crops [CC] and without cover crops [NCC]) effects on near‐surface soil physical, chemical, and hydraulic properties. Soil sample collection and in situ measurements were conducted, once per site, between May 2018 and May 2019 across four locations within the LMRV portion of eastern Arkansas. Overall and steady‐state infiltration rates were unaffected (p > .05) by cover‐crop treatment. Across all locations, extractable soil Na content in the top 10 cm was greater (p ≤ .05) with NCC (31.6 kg ha−1) compared with CC (21.6 kg ha−1). Averaged across treatment and soil depth (0 to 5 and 5 to 10 cm), water‐stable aggregate concentration in the 0.25‐ to 0.5‐ (0.101 g g−1) was 1.5 times greater (p ≤ .05) than that in the 1.0‐ to 2.0‐mm size class (0.068 g g−1). Though many soil properties did not significantly differ between CC treatments due to their collective variations, results of this study demonstrate the wide‐spread implications of CC use on physical, chemical, and hydraulic properties across a region.